Nigeria's indigenisation policy : proceedings of the November, 1974 symposium organized by the Nigerian Economic Society. - Nigerian Economic Society; Nigerian Economic Society (Ibadan, Nigeria : The Society, 1974)
This volume comprise of proceedings of the November, 1974 symposium organized by the Nigerian Economic Society on the subject "Indigenisation: what have we achieved?".
Bibliography: p. 66-67.
lje 6/3/19
Arch
Keywords: Indiginenisation; Economy-Nigeria; Nigeria